1979
DOI: 10.1051/jphyslet:019790040013029700
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of non-doped and doped polyacetylene films studied by E.S.R.

Abstract: Cis-polyacetylene films have been synthetized and doped with iodine and antimony penta fluoride, using usual chemical techniques. Doping, leads, after saturation, to conductivity values of about 120 and 25 (Ω cm) -1 at room temperature, respectively for I2 and SbF 5 dopants. The E.S.R. of cis- and trans-, non-doped and doped (CH)x films has been studied. A qualitative analysis of the results allows a better understanding of the electronic properties of these extremely non homogeneous and highly conductive dope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Moreover, it is very important to admit that conductivity measurements were carried out 24 h after iodine doping (doping time 1 h) in order to allow the doping to level off and reduce possible discrepancy in the doping level among the studied samples (even if it implied overall decrease of the measured conductivity). Available information about PA stability after oxygen treatment clearly indicates that conductivity rapidly decreases to values ten orders of magnitude lower 20,21 than found here for the ladder-like PA brushes. Moreover PA brushes retain the conductive abilities 6 months after their synthesis, while doped PA obtained in solution lose the ability to conduct electricity soon after a few hours.…”
Section: Electrical Properties Of Doped Poly(tpm) Brushesmentioning
confidence: 40%
See 1 more Smart Citation
“…Moreover, it is very important to admit that conductivity measurements were carried out 24 h after iodine doping (doping time 1 h) in order to allow the doping to level off and reduce possible discrepancy in the doping level among the studied samples (even if it implied overall decrease of the measured conductivity). Available information about PA stability after oxygen treatment clearly indicates that conductivity rapidly decreases to values ten orders of magnitude lower 20,21 than found here for the ladder-like PA brushes. Moreover PA brushes retain the conductive abilities 6 months after their synthesis, while doped PA obtained in solution lose the ability to conduct electricity soon after a few hours.…”
Section: Electrical Properties Of Doped Poly(tpm) Brushesmentioning
confidence: 40%
“…10 3 S cm −1 for doped poly-(p-phenylene), polyaniline, polythiophenes and about 10 2 S cm −1 for polypyrrole. 14,19,20 Electrical conductivity of non-doped conjugated chains strongly depends on their conformation and reaches a value of 10 −9 S cm −1 for cis-and 10 −6 S cm −1 for trans-PA. 21 Despite excellent and very promising conductive abilities, high instability of PA in air 22 and at elevated tempera-tures 23 as well as difficulties in its processing have significantly limited its application. Thus, PA has been rather discarded as an applicable conductive polymer and interest has been focused on other conjugated polymers of lower electrical conductivity but better stability and processability.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the possibility of the creation of a pair of solitons (polaron) has been evocated for light doping. Experimental results of magnetic [2,3] infrared [4,5] optical [6] and transport [7,8] measurements on doped (CH)x support the soliton mechanism for doping, while photoconductivity, light scattering and modulation spectroscopy experiments are consistent with a decay or the creation of soliton pairs [9,10]. In the series of experiments with various dopants, Fincher et al [11] found that upon dilute doping two new absorption modes appeared in the IR region at 1 370 and 900 cm-1.…”
Section: Introductionmentioning
confidence: 85%
“…One of the remarkable feature of trans-polyacetylene is its intrinsic neutral soliton defects (bond alternation domain walls) with spin properties, [47][48][49][50] and the magnetic moments of solitons can be detected by electron paramagnetic resonance (EPR). Here, we performed EPR characterization on these samples.…”
Section: Resultsmentioning
confidence: 99%